(3UhQI eKGd Ydi GdRGjQLI GdSHJjIs
(3ChdgG (B:s
(3GdMeO ddg hgPG UhQI eKJGd Ydi GdRGjQLI GdSHJjI s
(3BNQgG (B:s
(3CeG GdLOhd GdKGfj aSJQGg ef hQGA gPg GdhQbI Ef TGA Gdg JYGdi Bejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B46s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B(58 (3c(B) s
Keywords: (3GdMQha h GdChaGbs